The cartographic visualisation of spatial data. An example of nature protection areas in the Podlaskie Voivodship (north-eastern Poland) - Andruszkiewicz Anna; Korycka-Skorupa Jolanta (Polish Cartographical Review, 2020)
The authors attempt to visualise nature conservation issues in the Podlaskie Voivodship using a series of small-scale thematic maps. Publicly available spatial and statistical data was used. The authors discuss the effects of applying the adopted methodological solutions. Some of them present a new approach to cartographic visualisation of spatial data. It may be an opportunity to look at various visualisation methods, their effectiveness, and the possibility of visualising nature issues on small-scale thematic maps.